Conductive hydrogel luminal filler for peripheral nerve regeneration - Park, Junggeon; Kim, Junghyun; Choe, Goeun; Jung, Youngmee; Lee, Jae Young (Elsevier Science Inc., 2025)
Peripheral nerve injuries impair quality of life due to pain and loss of sensory and motor functions. Current treatments like autografts and nerve guidance conduits (NGCs) have limitations in functional restoration. Luminal fillers can enhance the effectiveness of NGCs by providing beneficial intraneural environments. In this study, we devised a novel injectable conductive luminal filler that allows for electrically active environments and efficient electrical stimulation of nerves. We developed injectable conductive hydrogel as a luminal filler for NGCs, composed of pluronic-coated reduced graphene oxide (rGO) and gelatin-based polymers, that gels spontaneously under physiological conditions. This filler combines nerve-like softness (0.31 +/- 0.02 kPa), appropriate conductivity (2.7 +/- 0.3 mS/cm), quick gelation (<5 min), and in vivo degradability. In a rat peripheral nerve defect model, the conductive hydrogel filler with electrical stimulation showed promising results in nerve regrowth, myelination, and functional recovery, performing comparably to autografts. This study underscores the potential of conductive fillers in enhancing nerve regeneration therapies.